Optimal piezoelectric beam shape for single and broadband vibration energy harvesting: modeling, simulation and experimental results - Abdul Muthalif, Asan Gani; Nordin, Nor Hidayati Diyana (Elsevier, 2015)
Harvesting energy from the surroundings has become a new trend in saving our environment. Among the established ones are solar panels, wind turbines and hydroelectric generators which have successfully grown in meeting the world’s energy demand. However, for low powered electronic devices; especially when being placed in a remote area, micro scale energy harvesting is preferable. One of the popular methods is via vibration energy scavenging which converts mechanical energy (from vibration) to electrical energy by the effect of coupling between mechanical variables and electric or magnetic fields. As the voltage generated greatly depends on the geometry and size of the piezoelectric material, there is a need to define an optimum shape and configuration of the piezoelectric energy scavenger. In this research, mathematical derivations for unimorph piezoelectric energy harvester are presented. Simulation is done using MATLAB and COMSOL Multiphysics software to study the effect of varying the length and shape of the beam to the generated voltage. Experimental results comparing triangular and rectangular shaped piezoelectric beam are also presented.